PENGARUH KAPASITAS INDIVIDU DAN AMBIGUITAS PERAN TERHADAP BUDGETARY SLACK - Bahrun, Sultan Adam; Idris, Hariany; Afiah, Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
This research aims to determine the influence of individual capacity and role ambiguity on budgetary slack. The variables in this research are Individual Capacity (X1) and Role Ambiguity (X2) as independent variables and budgetary slack (Y) as the dependent variable. The population in this study were employees within the Jeneponto Regency SKPD. The sample was selected using the Slovin formula and resulted in 92 respondents as the sample. The data collection technique used is a questionnaire. The data analysis techniques used are descriptive statistical tests, data quality tests, classical assumption tests, multiple linear regression analysis, F tests and coefficient of determination tests. The results of this research show that, based on the results of the descriptive analysis, individual capacity is 3.97 which is classified as high, role ambiguity is 4.49 which is classified as very high and budgetary slack is 4.51 which is classified as very high. From the results of the multiple linear regression test, the equation Y = 30,422 + 418 (X1) + (-117) (X2) is obtained, which means that for each additional value of individual capacity, the value of budgetary slack increases by 434 and for each additional value of role ambiguity, then the budgetary slack value decreased by -117. Based on the results of the t test, significant results were obtained at 0.001 0.05, which means that individual capacity has a significant effect on budgetary slack, thus the first hypothesis is accepted, and the results are significant at 0.209 0.05, which means that role ambiguity has no significant effect on budgetary slack, with Thus the second hypothesis is accepted. Meanwhile, the results of the analysis of the coefficient of determination (r2) obtained a value of (r2) = 0.468 or 46.8 percent. This shows that individual capacity and role ambiguity have an influence on budgetary slack of 46.8 percent, while the remaining 43.2 percent is influenced by other factors.Keywords: Individual Capacity, Role Ambiguity, Budgetary Slack